THE MISSING AGES IN “KUNG FU PANDA 3” MOVIE: A PSYCHOANALYTIC LITERARY CRITICISM - Kusen, Felicia Jessica; Silaen, Gwyneth Lillian; Aripin, Aileen Regina (Jurnal Pendidikan Makarios, 2023)
This study aims at showing the connection between Po’s past experiences and his present manifestations. This analysis intends to show the significance of the affection and primal parenting of both parents. A qualitative approach was employed to elucidate and evaluate the psychological concern depicted in this film. Given the narrative's visual medium, the utilization of cinematography in terms of camerawork served to articulate the storyline, environments, and characters. Additionally, the analytical framework of Sigmund Freud's "psychoanalysis" was adopted as the methodology for this examination, aiming to ascertain the sources of Po's anxiety as they relate to the phases of Freud's psychosexual development. As a result: 1) Po experiences anxiety due to the insufficient fulfillment of his 'id' during the oral stage, resulting in challenges in regulating his eating behavior, displaying pessimism, dependence, and heightened vulnerability to rejection. 2) The lack of parenting at the anal stage makes him manifest a lack of self-control, disorganized, messy and careless behaviors. 3) Po ultimately succeeds in building up his self-assurance.